Fat chance - 9 (New York : Putnan's, 1994)
In a series of diary entries, thirteen-year-old Judi recounts her struggles to lose weight, hide her bulimia from her mother, find a boy friend, and decide on a profession.
Keywords: Diaries -- Fiction; Weight control -- Fiction; Bulimia -- Fiction; Single-parent families -- Fiction; Jews -- United States -- Fiction